Ultrasonography Comparison of Diaphragm Morphological Structure and Function in Young and Middle-Aged Subjects with and without Non-Specific Chronic Low Back Pain: A Case-Control Study - Wenwu Xiao; Fuming Zheng; Ke Dong; Zhuangfu Wang; Yao Zu; Chuhuai Wang (Pain Research and Management)
Background. It is reported that impaired postural control in patients with non-specific chronic low back pain (NCLBP) was associated with “core” trunk muscle incoordination. However, as the diaphragm is an important component of the “core” deep trunk muscle group, we still know little about the potential relationship between diaphragm dysfunction and NCLBP. Objectives. This case-control study is intended to investigate the changes of diaphragm morphological structure and function in young and middle-aged subjects with and without NCLBP by ultrasound evaluation and its possible validity in predicating the occurrence of NCLBP. Methods. 31 subjects with NCLBP (NCLBP group) and 32 matched healthy controls (HC group) were enrolled in this study. The diaphragm thickness at the end of inspiration (Tins) or expiration (Texp) during deep breathing was measured through B-mode ultrasound, and the diaphragm excursion (Texc) was estimated at deep breathing through M-mode ultrasound. The diaphragm thickness change rate (Trate) was calculated by the formula: Trate=Tins−Texp/Texp×100%. Results. Compared with the HC group, the NCLBP group had a significant smaller degree of Tins (t = −3.90, P<0.001), Texp (Z = −2.79, P=0.005), and Trate (t = −2.03, P=0.047). However, there was no statistical difference in Texc between the two groups (t = −1.42, P=0.161). The binary logistic regression analysis indicated that Trate (OR = 16.038, P=0.014) and Texp (OR = 7.714, P=0.004) were potential risk factors for the occurrence of NCLBP. Conclusions. The diaphragm morphological structure and function were changed in young and middle-aged subjects with NCLBP, while the diaphragm thickness change rate (Trate) and diaphragm thickness at the end of expiration (Texp) may be conductive to the occurrence of NCLBP. Furthermore, these findings may suggest that abnormal diaphragm reeducation is necessary for the rehabilitation of patients with NCLBP.